Building an Ageless Mind: Preventing and Fighting Brain Aging and Disease - Tippett, William J. (Rowman & Littlefield Publishers, 2013)
By the year 2000 half of the people in the United States were over the age of 50. By 2030, 70 million elderly will account for 20% of the U.S. population. The percentage of the population with Alzheimer’s disease is significantly on the rise and by 2025 there will be a 45% increase in developed countries and a 215% increase in developing countries. Aging populations face many other issues involving cognitive decline. Building an Ageless Mind offers practical solutions, including specific directives to assist individuals in changing the course of cognitive decline as a result of aging and disease. The brain, our ability to think, and our self-concept are so very important to individual lives, and the desire to maintain robust cognitive function is the ultimate goal for anyone concerned about the aging mind. Here, Dr. William J. Tippett helps readers understand the basics of how the brain works, and explains why engaging in certain exercises may be helpful. He gives people the tools to maintain, combat, and understand good brain health. He also examines one of the most profound brain aging related illnesses of our time, Alzheimer’s disease, and provides detailed information on how this disease affects the individual, as well as ways to protect against it and to alter its course even if it’s been diagnosed. Lifestyle strategies to promote brain health are also offered throughout. Readers will be fascinated by the way the brain functions and ages, and the many methods available to everyone to maintain better brain health as they age.